Student Survey in Public Relations Services, Registration and Counseling, A Case Study of Petra University for the academic year 2013/2014. - الدليمي, عبد الرزاق محمد; سلطان, محمد صاحب (ALBAHITH ALALAMI, 2014)
The research discusses the public relations services, registration, and academic advising at Petra University for the years 2013-2014. Using a field study and surveying Petra University students to be informed about the services and to cover the tiny details that have to do with public relations role in the university as a specialized department interested in serving public and gaining their trust in terms of what is legal and possible to build and enhance the university reputation. And gain mutual trust between the university and its publics.The public relations is considered the main link which helps in organizing the relations between the senior management in the university and its staff and students.The same considering the academic advising and how the registration department helps the students by advising them and giving the suitable training to focalize the adaptation of the new students in the campus environment.This research focuses on these departments and the kinds of organized and helpful activities they give. The public relations stand on the front of these activities due it the imperative role it takes in the university sector.The public relations is considered an essential tool to achieve the development and growth of the academic and educational activities of the university and an essential part of an integration with the various parts and components of the organizational structure of the University.